Hambatan Guru Bimbingan dan Konseling dalam Pelaksanaan Layanan Bimbingan Kelompok di SMA Negeri 1 Dolok Masihul - Siti Fadilah Br Purba; Yenti Arsini; Alya Mahyani (Madani: Jurnal Ilmiah Multidisiplin, 2023)
In this study, the counselor's efforts to provide guidance group services are being distracted. The two principles that this study seeks to explain are: (1) comprehension in building a guiding group and (2) building a dynamics group. In this study, descriptive qualitative research was used. The basis for this study was two counselors, two students in class eleven, and one student vice. The researcher employs interviews in addition to a technique for data analysis based on the presentation and conclusion of the data. The study's findings are as follows: (1) The students' lack of attention to the counselor's explanations during guidance group is the primary source of the counselor's distraction when providing services for guidance groups, Students didn't interact to share their experiences since they didn't grasp the activity that was being done, creating a poor environment for the counselor. (2) The primary argument made by the counselor while assembling a dynamics group is that the school's facilitation was insufficient. The conclusion of this study is that in order for students to take use of guidance group services, counselors should increase their efforts to assist students in problem-solving with their peers.